Word prediction using closely and moderately related verbs in Down syndrome - Angulo-Chavira, Armando Q.; Castellón-Flores, Alejandra M.; Barrón-Martínez, Julia B.; Arias-Trejo, Natalia (Frontiers in Psychology, 2022)
People with Down syndrome (DS) have several difficulties in language learning, and one of the areas most affected is language production. Theoretical frameworks argue that prediction depends on the production system. Yet people with DS can predict upcoming nouns using semantically related verbs. Possibly, prediction skills in people with DS are driven by their associative mechanism rather than by the prediction mechanism based on the production system. This study explores prediction mechanisms in people with DS and their relationship with production skills. Three groups were evaluated in a preferential-looking task: young adults, children with DS, and a typically developing control group paired by sex and mental age. Participants saw two images, a target, and a distractor. They also heard a sentence in one of three conditions: with a verb that was closely related to the object (e.g., “The woman read the book”), with a verb that was moderately related to the object (e.g., “My uncle waited for the bus”), or with a verb that was unrelated to the object (e.g., “My sister threw a broom”). Their productive vocabulary was then measured. In the young adult and typically developing groups, the results showed prediction in sentences with highly and moderately related verbs. Participants with DS, however, showed prediction skills only in the highly related context. There was no influence of chronological age, mental age, or production on prediction skills. These results indicate that people with DS base prediction mainly on associative mechanisms, but that they have difficulty in generating top-down predictions.